Listeria monocytogenes and enterotoxigenic Staphylococcus aureus in dry fermented sausages belonging to "Traditional Agri‐Food Product" produced in Southern Italy. Issue 6 (22nd July 2019) - Quaglia, Nicoletta C.; Storelli, MariaMaddalena; Ioanna, Federica; Celano, Giuseppe; Celano, Gaetano V.; Conversano, Chiara; De Rosa, Michele; Dambrosio, Angela
Abstract: The aim of this study was to assess the microbiological quality and safety of typical dry fermented sausages produced in Apulia region, Southern Italy, classified as "Traditional Agri‐Food Products" (T.A.P.). A total of 106 samples were collected and analyzed. Two samples of Soppressata di maiale nero dei Monti Dauni (1.89%) were positive to Listeria monocytogenes . Nevertheless, the loads were <100 cfu/g hence all samples had a satisfactory microbiological quality. According to Gilbert's guidelines, 9.43% of the analyzed samples showed unsatisfactory microbiological quality since Staphylococcus aureus was between 100 and <10 4 cfu/g. Moreover, 7.54% of the dry fermented sausages analyzed had unacceptable microbiological quality since S. aureus loads were >10 4 cfu/g. Five isolated strains of S. aureus were enterotoxigenic. Based on findings, it is essential to apply and maintain good hygiene practices throughout the food chain, especially for T.A.P., which are often produced in small family processing plants using production protocols based on the experience handed down from father to son. Practical Application: The Traditional Agri‐Food Products (T.A.P.) are foodstuffs much appreciated by consumers because of their organoleptic qualities and taste that brings back to the genuine flavors of the past. The results of this study can contribute to the risk analysis for these particular products, and underline the need to apply and maintain good hygiene practices throughout the production chain.